The Criminalization of match-fixing in Kenya - Rabin, Roy Obure (Strathmore University, 2018)
There are many different definitions of sports however; I hold that sport is an institution which is a social behavior, the core of which is competition based on and individual or team skill and strategy. The specific behavior ranges from basic games children play to the serious competitions of professionals athletes. This institution extends deep through economics, education and even mass media to extents; it has been studied by various serious professions such as anthropologists, historians, economists, political scientists, social psychologists and authors in physical education. By virtue of spot1 being an institution, there have been attempts to study sports, by authors from the various numerous fields, from the perspective of the existing body of knowledge in their respective fields. With the commercialization of sports, as well as the increasingly high stakes involved, the study of sports has become a lucrative area for the legal profession too. The study of sports law or rather the law relating to sports creates an interface to study the relationship between society, the institution of sport and with the laws or legal principles. Dishonesty in sports goes a very long was back several decades back and although the occurrence primarily has its roots in commercial sports , various terms such as rigging or throwing games have been used to elaborate on it, there is no doubt that this fixing phenomenon has been around in sports for quite a long while
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Sports; Match-fixing; Throwing games; Athletes